Draining the Landscape: How Do Nitrogen Concentrations in Riparian Groundwater and Stream Water Change Following Milldam Removal?. Issue 8 (24th August 2021) - Lewis, Evan; Inamdar, Shreeram; Gold, Arthur J.; Addy, Kelly; Trammell, Tara L. E.; Merritts, Dorothy; Peipoch, Marc; Groffman, Peter M.; Hripto, Johanna; Sherman, Melissa; Kan, Jinjun; Walter, Robert; et al.
Abstract: Dam removals are on the increase across the US with Pennsylvania currently leading the nation. While most dam removals are driven by aquatic habitat and public safety considerations, we know little about how dam removals impact water quality and riparian zone processes. Dam removals decrease the stream base level, which results in dewatering of the riparian zone. We hypothesized that this dewatering of the riparian zone would increase nitrification and decrease denitrification, and thus result in nitrogen (N) leakage from riparian zones. This hypothesis was tested for a 1.5 m high milldam removal. Stream, soil water, and groundwater N concentrations were monitored over 2 years. Soil N concentrations and process rates and δ 15 N values were also determined. Denitrification rates and soil δ 15 N values in riparian sediments decreased supporting our hypothesis but no significant changes in nitrification were observed. While surficial soil water nitrate‐N concentrations were high (median 4.5 mg N L −1 ), riparian groundwater nitrate‐N values were low (median 0.09 mg N L −1 ), indicating that nitrate‐N leakage was minimal. We attribute the low groundwater nitrate‐N to denitrification losses at the lower, more dynamic, groundwater interface and/or dissimilatory nitrate reduction to ammonium (DNRA). Stream water nitrate‐N concentrations were high (median 7.6 mg N L −1 ) and contrary to our dam‐removal hypothesis displayed a watershed‐wide decline that was attributed to regional hydrologic changes. This study provided important first insights on how dam removals could affect N cycle processes in riparian zones and its implications for water quality and watershed management. Plain Language Summary: Dams are being removed to allow fish passage and improve safety for water users. Dam removal results in a drop of stream water level and a drying‐out of the streamside (riparian) zones. We investigated if these changes would undermine the N‐filtering service of riparian zones and increase N concentrations in groundwater and stream waters. We monitored soil and water N concentrations for 2 years following the removal of a 1.5 m milldam on Chiques Creek in Pennsylvania. Our data showed that while denitrification in soils did decrease, the N concentrations in riparian groundwaters and stream waters did not increase over the study period. Key Points: The effect of dam removal on riparian zone nitrogen (N) cycle processes and groundwater N concentrations is unknown We studied changes in riparian N cycle processes associated with the removal of a 1.5 m milldam for 2 years While soil denitrification and δ 15 N decreased following dam removal, an increase in groundwater nitrate‐N concentrations was not observed